CONTENT ANALYSİS OF ARTİCLES AND THESES ABOUT TEACHER MOTİVATİON - Emiroğlu, Osman; Burgul, Nazım; Savaşan, Ahmet; Akdağ, Şahin (Revista Inclusiones, 2019)
The subject of motivation is encountered in many areas where living things exist. In this context, the motivation factor is a very important issue for the teacher element in the education and training process. The increasing motivation of teachers is very important for the top management of schools. This importance activates students and other motivational factors that take part in the core of the education and training process. As a result of the research, it is revealed that it is necessary to be motivated both students and teachers and the motivated teachers provide more participating students for in-class activities. As specified in the body of literature, many pieces of research are examined in this subject. While the research is conducted, the literature review method is used, theses and articles are examined. Totally 72 articles are reviewed, it is observed that behaviour of the management has a strong and determinant role on the motivation of teachers. It is observed that the subject of leadership is frequently studied in the articles that mostly examined in the teacher motivation. In this regard, long-term researches should be performed for evaluation of the teacher motivation development boundedness.